2022
DOI: 10.1002/jeq2.20440
|View full text |Cite
|
Sign up to set email alerts
|

Copper induces nitrification by ammonia‐oxidizing bacteria and archaea in pastoral soils

Abstract: Copper (Cu) is the main co‐factor in the functioning of the ammonia monooxygenase (AMO) enzyme, which is responsible for the first step of ammonia oxidation. We report a greenhouse‐based pot experiment that examines the response of ammonia‐oxidizing bacteria and archaea (AOB and AOA) to different bioavailable Cu concentrations in three pastoral soils (Recent, Pallic, and Pumice soils) planted with ryegrass (Lolium perenne L.). Five treatments were used: control (no urine and Cu), urine only at 300 mg N kg−1 so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Besides microbial toxicity, increasing Cu levels in soils can influence other microbial-mediated processes, such as nitrification rate. Matse et al [38] reported that increasing bioavailable Cu in soils can have a negative influence on nitrification bacteria, thus, influencing nitrogen use efficiency.…”
Section: Importance Of These Results In Orchard Managementmentioning
confidence: 99%
“…Besides microbial toxicity, increasing Cu levels in soils can influence other microbial-mediated processes, such as nitrification rate. Matse et al [38] reported that increasing bioavailable Cu in soils can have a negative influence on nitrification bacteria, thus, influencing nitrogen use efficiency.…”
Section: Importance Of These Results In Orchard Managementmentioning
confidence: 99%